Quality of Life 1 Year after Aneurysmal Subarachnoid Hemorrhage in Good Outcome Patients Treated by Clipping or Coiling - Preiss, Marek; Netuka, David; Koblihova, Jana; Bernardova, Lenka; Charvat, Frantisek; Kratochvilova, Dominika; Benes, Vladimír (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background and Purpose A study was conducted to compare the quality of life (QOL) of surgically versus endovascularly treated patients with ruptured cerebral aneurysms.Methods We treated 45 patients surgically (surgical clipping [SC] group) and 44 by endovascular therapy (coil embolization [CE] group). A standardized test of QOL and a structured interview were employed to assess changes 1 year after subarachnoid hemorrhage (SAH). One neurosurgical team using the same treatment protocols treated all patients. The SC and CE groups did not differ significantly in age, sex, education, aneurysm size, Hunt and Hess grade, Glasgow outcome scale (GOS) score, and intelligence quotient (IQ).Results Generally, the patients reported psychological changes (impairment in memory, 47%; concentration, 20%; and ability to learn new things, 12%), which they subjectively related to SAH. On the one hand, 31% of the patients believed that close relatives noticed changes in their psychological condition as a result of the intervention. On the other hand, 61% reported an unaltered economic situation, 51% were well adjusted in work, and 70% claimed their family relationships remained unchanged. In comparison with the controls, patients claimed to have lower QOL in the areas of sexuality, love, psychic well-being, physical autonomy, and health. No differences in QOL were found between the SE and CE groups.Conclusions The differences in QOL in the patients treated by either coiling or clipping were small and nonsignificant. Participants in both groups mentioned lower QOL in the areas of intimate relationships and health.
Keywords: subarachnoid hemorrhage; surgical clipping; coiling embolization; quality of life